Question
upstudy study bank question image url

\( 1 \leftarrow \quad \) Solve the following equation by the square root method. \[ (x-6)^{2}=9 \]

Ask by French Erickson. in the United States
Jan 13,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 3 \) and \( x = 9 \).

Solution

To solve the equation \( (x - 6)^{2} = 9 \) using the **square root method**, follow these steps: ### Step 1: Take the Square Root of Both Sides Apply the square root to both sides of the equation. Remember that taking the square root introduces both the positive and negative roots. \[ \sqrt{(x - 6)^{2}} = \sqrt{9} \] ### Step 2: Simplify Both Sides The square root of a squared term simplifies to the absolute value of the original expression. Also, calculate the square root of 9. \[ |x - 6| = 3 \] ### Step 3: Remove the Absolute Value The equation \( |x - 6| = 3 \) implies two possible scenarios: 1. \( x - 6 = 3 \) 2. \( x - 6 = -3 \) ### Step 4: Solve for \( x \) in Each Scenario **Scenario 1: \( x - 6 = 3 \)** \[ x = 3 + 6 \\ x = 9 \] **Scenario 2: \( x - 6 = -3 \)** \[ x = -3 + 6 \\ x = 3 \] ### Step 5: State the Solutions The equation has two solutions: \[ x = 3 \quad \text{and} \quad x = 9 \] ### Verification To ensure that both solutions are correct, substitute them back into the original equation. **For \( x = 3 \):** \[ (3 - 6)^{2} = (-3)^{2} = 9 \quad \checkmark \] **For \( x = 9 \):** \[ (9 - 6)^{2} = (3)^{2} = 9 \quad \checkmark \] Both values satisfy the original equation.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( (x-6)^{2}=9 \) using the square root method, you first take the square root of both sides. This gives you two cases to consider: 1. \( x - 6 = 3 \) 2. \( x - 6 = -3 \) Now, solve for \( x \) in each case: For the first equation: \[ x - 6 = 3 \] \[ x = 3 + 6 \] \[ x = 9 \] For the second equation: \[ x - 6 = -3 \] \[ x = -3 + 6 \] \[ x = 3 \] Therefore, the solutions to the equation \( (x-6)^{2}=9 \) are \( x = 9 \) and \( x = 3 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy